Occupational Therapy Practice in Mainstream Schools: Results from an Online Survey in Switzerland - Vera C. Kaelin; Sylvie Ray-Kaeser; Stefania Moioli; Cornelia Kocher Stalder; Lietta Santinelli; Angelika Echsel; Christina Schulze (Occupational Therapy International)
The shift towards inclusive education in many European countries has led to structural changes that affect both schools and their related professionals aiming to support children’s participation. While most European countries acknowledge inclusive education and its need, serious challenges exist to its implementation at a national and local community level. Interdisciplinary collaboration, including health and educational professionals, is seen as an imperative key principle for inclusive education services. To learn about the occupational therapist’s contribution to inclusive education, the aim of this study was to describe the state of the art of occupational therapists’ collaboration and services delivery in Swiss schools. Using an exploratory, cross-sectional study design, a web-based survey was sent to 509 occupational therapists in Switzerland resulting in 302 responses for data analysis using descriptive statistics. Findings show that nearly all participants (97%) collaborate with schools, and 49% of participants provided direct services within a mainstream school setting. These services were mainly funded by health insurance and focused on physical and social environmental adaptations. Despite reported collaboration between occupational therapists and schools, this study shows a need for changes in federal health and education legislation as well as innovative solutions for service delivery in schools.